2019
DOI: 10.3390/nu11071585
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Omega-3 Fatty Acids in Human Milk Is Related to Their Habitual but Not Current Intake

Abstract: This study determined fatty acid (FA) concentrations in maternal milk and investigated the association between omega-3 fatty acid levels and their maternal current dietary intake (based on three-day dietary records) and habitual dietary intake (based on intake frequency of food products). Tested material comprised 32 samples of human milk, coming from exclusively breastfeeding women during their first month of lactation. Milk fatty acids were analyzed as fatty acid methyl ester (FAME) by gas chromatography usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 63 publications
(83 reference statements)
2
44
0
Order By: Relevance
“…As result, it can be concluded that BM metabolites vary during the first month of lactation and the highest variability has been shown in pre-term samples [20]. In a recent study, Bzikowska-Jura and co-workers [64] investigated FAs levels in BM, determining omega-3 FA content in relation to maternal current dietary intake. N=32 samples from n=32 women during the first month of lactation were analyzed with GC-MS.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…As result, it can be concluded that BM metabolites vary during the first month of lactation and the highest variability has been shown in pre-term samples [20]. In a recent study, Bzikowska-Jura and co-workers [64] investigated FAs levels in BM, determining omega-3 FA content in relation to maternal current dietary intake. N=32 samples from n=32 women during the first month of lactation were analyzed with GC-MS.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As result, current dietary intake of omega-3 FAs was not significantly correlated with BM content, while their habitual intake could influence BM levels. Nutritional habits in the three months prior delivery mainly affect BM [64].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The impact of physiological factors, e.g., sequential stages of lactation [ 8 , 9 ], pre-/post-feed [ 10 ] and daytime [ 11 ] is the best investigated. Changes in maternal diet [ 12 , 13 , 14 ] and nutritional status [ 15 , 16 ] also significantly influence HM composition, mainly within the lipid fraction. Likewise, the concentrations of non-nutritive milk components (e.g., hormones, steroids, growth and satiety factors) are affected by maternal factors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the similarities in MFGM proteome, the composition of bovine milk differs from human milk. An example is the content of essential unsaturated fatty acids, which is higher in human milk than in bovine milk because of the high rate of biohydrogenation processes of dietary unsaturated fatty acids in the rumen-α-linolenic acid shows a lower difference (0.5-2% and 1-2% of total milk FAs for bovine and human milk fat, respectively) than linoleic acid (1-3% and 8-18% of total milk FAs for bovine and human milk fat, respectively) [25,29,82,83]. In addition to nutrients, human breast milk also contains several bioactive compounds (Igs, enzymes, hormones) and live cells (e.g., leucocytes) that cannot be easily added to IFs [79,84].…”
Section: Itemmentioning
confidence: 99%